2014
DOI: 10.1534/genetics.114.163311
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Biased Gene Expression and Evolution of the X Chromosome in Nematodes

Abstract: Studies of X chromosome evolution in various organisms have indicated that sex-biased genes are nonrandomly distributed between the X and autosomes. Here, to extend these studies to nematodes, we annotated and analyzed X chromosome gene content in four Caenorhabditis species and in Pristionchus pacificus. Our gene expression analyses comparing young adult male and female mRNAseq data indicate that, in general, nematode X chromosomes are enriched for genes with high female-biased expression and depleted of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
128
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(145 citation statements)
references
References 138 publications
12
128
0
Order By: Relevance
“…Consistent with this, transcriptional profiling in C. elegans revealed a significant underrepresentation of meiosis and sperm-expressed genes on the X (Reinke et al 2000). It is likely that this underrepresentation of meiosis and spermatogenesis genes is also true of the Caenorhabditis group as a whole as there is a high degree of synteny between the X chromosomes in those species with good genomic assemblies (Hillier et al 2007;Fierst et al 2015) and expression analyses have uncovered a depletion of malebiased expressed genes on the X chromosome of C. briggsae, C. remanei, C. brenneri, as well as the more distantly related Pristionchus pacificus (Albritton et al 2014).…”
Section: Why Meiotic Silencing In Caenorhabditis?mentioning
confidence: 99%
“…Consistent with this, transcriptional profiling in C. elegans revealed a significant underrepresentation of meiosis and sperm-expressed genes on the X (Reinke et al 2000). It is likely that this underrepresentation of meiosis and spermatogenesis genes is also true of the Caenorhabditis group as a whole as there is a high degree of synteny between the X chromosomes in those species with good genomic assemblies (Hillier et al 2007;Fierst et al 2015) and expression analyses have uncovered a depletion of malebiased expressed genes on the X chromosome of C. briggsae, C. remanei, C. brenneri, as well as the more distantly related Pristionchus pacificus (Albritton et al 2014).…”
Section: Why Meiotic Silencing In Caenorhabditis?mentioning
confidence: 99%
“…Previous studies indicate up to 60% of all genes show sex-biased expression [in mice (Khil et al 2004;Yang et al 2006;Reinius et al 2012), flies (Parisi et al 2003;Ranz et al 2003;Allen et al 2013;Kaiser and Bachtrog 2014), and nematodes (Reinke et al 2004;Thomas et al 2012;Albritton et al 2014)]. Previous genome-wide studies found that compared to autosomes, the X chromosome generally harbors more genes with female-biased expression and fewer genes with malebiased expression [in mice (Khil et al 2004;Yang et al 2006;Reinius et al 2012), flies (Parisi et al 2003;Ranz et al 2003), and nematodes (Reinke et al 2004;Thomas et al 2012;Albritton et al 2014)]. However, this observed enrichment of female bias and depletion of male bias from the X is a generalization that may not apply universally to every tissue type or developmental stage.…”
mentioning
confidence: 99%
“…Similar results were observed using expression cutoffs of 0.1 FPKMs and 10 FPKMs to determine expressed genes ( Figure S1). Compared to adults (Thomas et al 2012;Albritton et al 2014), there were fewer genes showing sex-biased expression in L3 larvae (Figure 2A). This result is expected, as most sexually dimorphic tissues develop after the L3 stage (Kimble and Hirsh 1979).…”
mentioning
confidence: 99%
See 2 more Smart Citations